Indifferent minds, broken system: a critical examination of mental health care provision for Spain’s incarcerated population with serious mental illnesses - Calcedo-Barba, Alfredo; Antón Basanta, Joaquín; Paz Ruiz, Silvia; Muro Alvarez, Alvaro; Elizagárate Zabala, Edorta; Estévez Closas, Verónica; López López, Angeles; Barrios Flores, Luis Fernando (Frontiers in Psychiatry, 2024)
Spain healthcare system is decentralized, with seventeen autonomous regions overseeing healthcare. However, penitentiary healthcare is managed nationally, except in Catalonia, the Basque Country, and Navarra. These variations impact mental health care provision for inmates with serious mental illness (SMI).To delineate differences between regions in terms of mental health care provision for individuals with SMI, available resources, and the perspectives of healthcare professionals operating in the Spanish prison environment.Employing an explanatory sequential mixed-method approach, the study conducted an extensive literature review, quantitative data collection through structured questionnaires, and qualitative data collection via focus groups and four in-depth interviews. Analysis involved calculating percentages and ratios for quantitative data and thematic analysis for qualitative data interpretation to comprehensively understand mental healthcare provision.In December 2021, about 4% of inmates in Spain had SMI. There are three distinct models of mental healthcare within the Spanish prison system. The traditional penitentiary model, representing 83% of the incarcerated population, operates independently under the General Secretariat of Penitentiary Institutions at a national level. This model relies on an average of 5.2 penitentiary General Practitioners (pGP) per 1,000 inmates for psychiatric and general healthcare. External psychiatrists are engaged for part-time psychiatric assessment. Acute psychiatric hospitalization occurs in general nursing modules within penitentiary centers or in Restricted Access Units (RAUs) in reference hospitals. Two penitentiary psychiatric hospitals provide care to unimputable SMI inmates from all over Spain. Innovative penitentiary models, constituting 17% of the prison population, integrate penitentiary healthcare within regional public health systems. The Basque Country features a Mental Health Unit with full-time care teams within the penitentiary center. Catalonia emphasizes community care, providing full-time dedicated psychiatric services within and outside prisons, ensuring continued care in the community. Both models prioritize personnel with specialized mental health training and compensation akin to non-prison healthcare settings.Regional disparities in penitentiary mental healthcare models in Spain result in resource inequalities, impacting specialized care for inmates with SMI and opportunities for healthcare professionals. The models in the Basque Country and Catalonia offer valuable experiences for penitentiary healthcare.